Conceptual Model Design of Assistances System Development for Informatics Proficiency TestBased on Ubiquitous Learning - RanggaFirdaus, BasukiWibawa, Khaerudin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Thedevelopment ofInformation and Communication Technologyiscurrentlyinfluencing graduates'competencies ineveryIndonesiaUniversity. Someofthephenomena obtainedinthefieldboth technicallyandnon-technicalinclude:Therearestillfew andtendtohavenoinformationfromthecampusrelated tothecompetenceoflecturersandstudentsinthefieldof informatics. Minimalinformation onthecollaboration between thecampus worldandindustrial fields published inthemedia.Cooperation betweencampus withprofessional associations andindustryassociations inimplementing thelinkandmatch,especiallyin curriculum development,feelargeenoughinfollowing thecertificationtestprofessionalsininformatics,yetseen asystemthatactsasanaggregator,asystemthatbridges between industry andthefieldofcampus. The characteristicsmodeldevelopedinthisresearchbroadly combines threemodelsofinterrelated system development betweentheBorgandGallmodelasthe backbone, Hanafin, andPack asthelearninginteraction process,andthewaterfall modelasthemakingofthe mentoringapplication system.Thefinalresultofthe researchistheestablishmentofconceptualmodeldesign in adigitallearningsystemfromacertificationprogram based onthe IndustrialProfessionaland Association fields.